The Emerging Role of Exosomes in Oral Squamous Cell Carcinoma - Lu, Yanhui; Zheng, Zhichao; Yuan, Yunyi; Pathak, Janak L.; Yang, Xuechao; Wang, Lijing; Ye, Zhitong; Cho, William C.; Zeng, Mingtao; Wu, Lihong (Frontiers in Cell and Developmental Biology, 2021)
The oral cancers constitute approximately 2% of all cancers, while the most common type of oral squamous cell carcinoma (OSCC) represents 90% oral cancers. Advanced-stage OSCC tends to metastasize to lymph nodes. Although the treatment of OSCC has improved recently, it still has a high rate of local recurrence and poor prognosis, with a five-year survival rate of only 50%. Thus, exploring new therapeutic strategies for OSCC is therefore an urgent priority. Exosomes, the small membrane vesicles derived from endosomes, have been detected in a wide array of bodily fluids. Exosomes contain a diversity of proteins, mRNAs, and non-coding RNAs, including microRNAs, long non-coding RNAs, piRNAs, circular RNAs, tsRNAs, and ribosomal RNAs, which are delivered to neighboring cells or transported to distant sites. Exosomes have been associated with the tumorigenesis of OSCC, and promote the proliferation, colonization, and metastasis of OSCC by transferring their contents to target cells. Furthermore, exosomes are involved in the regulation of the tumor microenvironment to transform healthy conditions to conditions favoring cancer progression in vivo. In this review, we summarize recent progress on the role of exosomes in the tumorigenesis and progression of OSCC and focus on the potential for therapeutic applications of exosomes in OSCC.